Antimicrobial Activities of the Leaves and Fruits of (Cassia fistula) - Kadam, Rabha,M. G.; Abdel-Rahim, Awad M.; Yassin, Atif, A.A. (Gezira Journal of Engineering and Applied Sciences, 2021)
The biological activity of the extracts of the leaves and fruits of C . fistula tree, was tested against both fungi ( Aspergillus niger and Penicillium digitatum ), and two bacteria ( Staph. aureus and E. coli ). From the results it is clear that the leaf extracts were effective against the radial growth of the two fungi. For P. digitatum it was 1.0 mm at 100% concentration compared to 2.2 mm at the control treatment (0.0% concentration) at the 8 th day. However, for A. niger it was only 0.5 mm at 100% concentration compared to 2.3 mm at the control treatment (0.0% concentration) at the 8 th day. The results also showed that the fruit extracts of C. fistula were also effective in inhibiting the radial  growth of  both fungi, although the extracts are more effective against A. niger than P. digitatum , they gave complete inhibition at all of the concentrations The growth was inhibited even from the second day. The effects of the leaf and fruit extracts of C. fistula were also examined on the fresh and dry weights of both fungi ( P. digitatum and A. niger ). The leaf extracts were found very effective at their higher concentration compared to the control treatment. However the leaf extracts are better compared to the fruit extracts. The inhibition zone tests were also included in the present study, to evaluate the effect of the leaf and the fruit extracts of the C. fistula tree on inhibiting the growth of two bacteria (the Gram positive, Staph. aureus and the Gram negative, E. coli ). The results indicated that the extracts were very effective in inhibiting the growth of the bacterium both bacteria. They gave 10.0 mm 9.0 mm inhibiting zones, for Staph. aureus and 13.0 mm and 11.0 mm inhibiting zones for   E. coli , respectively.